Risk analysis XI - Mambretti, S.; Fabbri, A. (WIT transactions on engineering sciences, 2019)
Containing papers from the 11th International Conference on Computer Simulation in Risk Analysis and Hazard Mitigation 2018, this book will be of interest to those concerned with all aspects of risk management and hazard mitigation, associated with both natural and anthropogenic hazards.